2014
DOI: 10.1002/app.40580
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of histocompatibility of silk fibroin/polyurethane membrane with controlled release of aspirin

Abstract: The histocompatibility of polyurethane (PU) modified by superfine silk-fibroin (SF) powder (1 : 1) with different dosage of aspirin to determine the best dosage for histocompatibility was investigated. Aspirin powder was incorporated into SF-PU (1 : 1) blend mixture at doses of 0%, 5%, or 10% (w/w). The influence of different doses of aspirin on histocompatibility of the hybrid material was studied by using morphology examination, infrared spectroscopy, in vitro drug release study, and in vivo tests including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Due to the advantages of superfine technology, fibroin powder is currently being explored as a green alternative for preparing regenerated materials. Typically, fibroin powder is blended with a synthetic polymer, especially polyurethane, to meet the diversity of demand for functional materials owing to their improved mechanical properties. , Different superfine fibroin powder/polyurethane-based materials have been demonstrated in our previous studies (Figure ), i.e., breathable textile coatings, bionic fibers, efficient dye sorbents for removing dyes from textile effluents, drug delivery for controlling heparin release, and small-diameter vascular tubular materials with high biocompatibility to blood both in vivo and in vitro . However, despite the remarkable potential and diversity of fibroin powder blends, their applications have been limited by challenges including poor mechanical properties and brittleness associated with a high concentration of superfine fibroin powders. Recently, researchers have tried to improve the mechanical properties of silk fibroin blends by plasma treatment, but unfortunately, the results are not satisfactory .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the advantages of superfine technology, fibroin powder is currently being explored as a green alternative for preparing regenerated materials. Typically, fibroin powder is blended with a synthetic polymer, especially polyurethane, to meet the diversity of demand for functional materials owing to their improved mechanical properties. , Different superfine fibroin powder/polyurethane-based materials have been demonstrated in our previous studies (Figure ), i.e., breathable textile coatings, bionic fibers, efficient dye sorbents for removing dyes from textile effluents, drug delivery for controlling heparin release, and small-diameter vascular tubular materials with high biocompatibility to blood both in vivo and in vitro . However, despite the remarkable potential and diversity of fibroin powder blends, their applications have been limited by challenges including poor mechanical properties and brittleness associated with a high concentration of superfine fibroin powders. Recently, researchers have tried to improve the mechanical properties of silk fibroin blends by plasma treatment, but unfortunately, the results are not satisfactory .…”
Section: Introductionmentioning
confidence: 99%
“…Illustration of fabricating fibroin powder and its applications. ,, (Reprinted with permission from ref . Copyright 2014, Elsevier.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has investigated the histocompatibility of NSFP-modified biomedical polyurethane (BPU) used in conjunction with different dosages of aspirin. We found that NSFP + aspirin enhanced the antiinflammatory and anti-platelet effects as well as the histocompatibility of BPU membranes, 15 although the precise factors responsible for the improvement in BPU biocompatibility was difficult to determine due to the presence of aspirin. Human umbilical vein endothelial cells (HUVECs) grown on the surface of NSFP-modified BPU membranes showed good spreading and adhesion.…”
Section: Introductionmentioning
confidence: 90%
“…This method involves chopping fibers with a suitable cutter, and crushing them in a grinding unit to obtain silk fibroin particles of the desired diameter. 12,13 As is known, silk fibroin particles prepared by dissolving-regeneration do not satisfy many requirements for bio-related applications owing to their partial solubility in water. However, the silk fibroin particles prepared by the mechanical method could overcome this solubility limitation in water.…”
mentioning
confidence: 99%